BODIPY: A Highly Versatile Platform for the Design of Bimodal Imaging Probes1. Issue 37 (23rd July 2015) - Lhenry, Damien; Larrouy, Manuel; Bernhard, Claire; Goncalves, Victor; Raguin, Olivier; Provent, Peggy; Moreau, Mathieu; Collin, Bertrand; Oudot, Alexandra; Vrigneaud, Jean‐Marc; Brunotte, François; Goze, Christine; et al.
Abstract In molecular imaging, multimodal imaging agents can provide complementary information, for improving the accuracy of disease diagnosis or enhancing patient management. In particular, optical/nuclear imaging may find important preclinical and clinical applications. To simplify the preparation of dual‐labeled imaging agents, we prepared versatile monomolecular multimodal imaging probe (MOMIP) platforms containing both a fluorescent dye (BODIPY) and a metal chelator (polyazamacrocycle). One of the MOMIP was conjugated to a cyclopeptide (i.e., octreotide) and radiolabeled with 111In. In vitro and in vivo studies of the resulting bioconjugate were conducted, highlighting the potential of these BODIPY‐based bimodal probes. This work also confirmed that the biovector and/or the bimodal probes must be chosen carefully, due to the impact of the MOMIP on the overall properties of the resulting imaging agent.